Migration of Rich Immigrants Gender, Ethnicity, and Class - Vailati, Alex.; Rial, Carmen; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
Migration of Rich Immigrants addresses flows of emigrants who establish themselves in other countries temporarily or permanently, in favorable economic conditions. Vailati and Rial explore these migratory paths and analyze how gender, class, age, sexual orientation and ethnicity influence these processes.
Keywords: Social sciences; Ethnology; Anthropology; Sociology; Ethnicity; Emigration and immigration; Social Sciences; Social Anthropology; Cultural Anthropology; Migration; Sociology, general; Ethnicity Studies; Anthropology; Electronic books